Konstruksi Sosial Penerapan Nilai-Nilai Pancasila Santri Mahasiswa Pondok Pesantren Al-Amien Rejomulyo Kota Kediri - Syarifuddin, Amir; Huda, Muhammad Qomarul; Zuhdi, Muhammad (Spiritualita, 2021)
Islamic boarding schools as educational institutions are also responsible for preparing students to face the demands of the times in this modern era. Of course, in religious learning, students are also given insight into understanding the values of Pancasila. For this reason, the focus of this research is: 1) What is the process of social construction of Pancasila values for students of Al-Amien Islamic Boarding School? 2) How are the values of Pancasila for the students of the Al-Amien Islamic boarding school applied? This study uses a qualitative approach with the type of field research (field research). Data collection methods that researchers use in this study include the methods of observation, interviews, and documentation. And in analyzing, the researcher uses three steps, namely data reduction, data display, then draw conclusions or verification. Based on the research conducted, the researcher can conclude that the application of Pancasila values. Namely: mutual tolerance, mutual respect, mutual help, doing good, is a small picture of the application of Pancasila values in Islamic boarding schools, which has the aim of training students in the application of Pancasila values while strengthening the friendship of a student, and also maintaining the integrity of the Unitary Republic of Indonesia. The purpose of the research is the first to find out how the application of Pancasila values in the daily life of students. The second is to find out how students understand the values of Pancasila.